Perforator Flap: A Changing Paradigm for The Reconstructive Plastic Surgery in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Abstract not availableJ Bangladesh Coll Phys Surg 2021; 39(2): 78-79